2013
DOI: 10.1189/jlb.1012543
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammasome-derived IL-1 in driving IL-17 responses

Abstract: NLRs are members of the PRR family that sense microbial pathogens and mediate host innate immune responses to infection. Certain NLRs can assemble into a multiprotein complex called the inflammasome, which activates casapse-1 required for the cleavage of immature forms of IL-1␤ and IL-18 into active, mature cytokines. The inflammasome is activated by conserved, exogenous molecules from microbes and nonmicrobial molecules, such as asbestos, alum, or silica, as well as by endogenous danger signals, such as ATP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 138 publications
(155 reference statements)
3
93
0
5
Order By: Relevance
“…In inflammatory diseases, such as psoriasis, it has been shown that the presence of "inflammasome related" cytokines such as IL 1 and IL 18 could synergize with IL 23 to promote Th17 cell differentiation (Mills et al, 2013). In Tg KLK5 skin, we found elevated expression of Il 1, Il 18, and Il 23, which could explain the presence of Th17 cells.…”
Section: Discussionmentioning
confidence: 64%
“…In inflammatory diseases, such as psoriasis, it has been shown that the presence of "inflammasome related" cytokines such as IL 1 and IL 18 could synergize with IL 23 to promote Th17 cell differentiation (Mills et al, 2013). In Tg KLK5 skin, we found elevated expression of Il 1, Il 18, and Il 23, which could explain the presence of Th17 cells.…”
Section: Discussionmentioning
confidence: 64%
“…We used RNA from Jurkat, a human T cell lymphoma line that does not produce inflammatory cytokines as our base control, and for comparison, RNA from the CD41 − population derived along with the MKp from the day 5–6 HSPC cultures that would contain myeloid/DC progenitors, as well as RNA from PMA-stimulated THP1 cells, a human macrophage cell line. MKp from three different donors tested (among the nine used in this study)-, expressed mRNA for Th17-inducing cytokines, such as IL-1, IL-18 IL-6, TGF-β, and IL-23; the first two of which being especially important for human Th17-induction [16,17] were expressed at high levels by the MKp, comparable to PMA-stimulated THP1 cells (Fig. 2A).…”
Section: Resultsmentioning
confidence: 98%
“…MKp from different donors expressed transcripts for Th17-inducing cytokines, including IL-6, TGFβ and IL-23, but most pronounced was the expression of IL-1 and IL-18, which are especially important for human Th17-induction [16,17]. Moreover, MKp highly expressed mRNA for other mediators of Th17 induction, such as BAFF, and COX2 (PTGS2); the latter mediating PGE2 production [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated NF-κB translocates to the nucleus and induces the transcription of pro-inflammatory cytokines [11]. IL-1-targeted drugs, such as the IL-1 receptor antagonist anakinra and the neutralizing monoclonal anti-IL-1β antibody canakinumab, result in a rapid and sustained remission in inflammatory diseases [12]. Daily injections of IL-1 receptor antagonist (IL-1ra) decreased the severity of clinical EAMG in C57BL/6 mice with suppressed serum IFN-γ, TNF-α, IL-1β, C3, and anti-AChR IgG1 [13].…”
Section: Introductionmentioning
confidence: 99%